(untitled) - Patterson, David A. (Amsterdam, 2005)
This book is very interesting and speaks to the students who would like to feel a connection between classroom materials and real-world applications. This revision is well-updated and a comprehensive introduction to the hardware and software fundamentals.
Keywords: Computer organization,Computer engineering,Computer interface